2019
DOI: 10.1038/s41467-019-10479-4
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Slug represses p16Ink4a and regulates murine muscle stem cell aging

Abstract: Activation of the p16 Ink4a -associated senescence pathway during aging breaks muscle homeostasis and causes degenerative muscle disease by irreversibly dampening satellite cell (SC) self-renewal capacity. Here, we report that the zinc-finger transcription factor Slug is highly expressed in quiescent SCs of mice and functions as a direct transcriptional repressor of p16 Ink4a . Loss of Slug promotes der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Specific analysis of the p16INK4a locus in satellite cells isolated from geriatric muscles revealed the loss of ubiquitinated H2A, a chromatin repressive mark associated with the polycomb repressor complex 1 . More recently, the transcriptional repressor Slug was also found to be downregulated in aged satellite cells, contributing to the derepression of the p16INK4a gene and the conversion of aged muscle stem cells to a pre‐senescent state . Future studies of global chromatin accessibility will likely reveal other changes to specific genomic loci that trigger age‐related perturbations in satellite cell function.…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
See 1 more Smart Citation
“…Specific analysis of the p16INK4a locus in satellite cells isolated from geriatric muscles revealed the loss of ubiquitinated H2A, a chromatin repressive mark associated with the polycomb repressor complex 1 . More recently, the transcriptional repressor Slug was also found to be downregulated in aged satellite cells, contributing to the derepression of the p16INK4a gene and the conversion of aged muscle stem cells to a pre‐senescent state . Future studies of global chromatin accessibility will likely reveal other changes to specific genomic loci that trigger age‐related perturbations in satellite cell function.…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
“…). These manipulations include genetic interventions to silence p16INK4a expression, thereby restoring quiescence and regenerative capacity to the aged satellite cell . Similarly, ex vivo pharmacological inhibition of p38 MAPK signaling decreases the expression of cell‐cycle inhibitors, such as p16INK4a, and restores asymmetric division in satellite cells, contributing to enhanced regenerative potential of aged satellite cells in muscle transplantation experiments .…”
Section: Interventions For Satellite Cell Rejuvenationmentioning
confidence: 99%
“…The finding of decreased muscle mass in FoxM1-cKO mice prompted us to examine the abundance of SCs in the skeletal muscle. Since SCs have definite cell surface markers (defined as CD45 − Sca1 − CD11b − CD31 − CD34 + α 7-integrin + ) 31 , we utilized flow cytometry to analyze the SC pool. FoxM1 deletion had no obvious effect on the abundance of SCs in 2-month-old mice ( Supplementary Fig.…”
Section: Foxm1 Deficiency Impairs Sc Maintenance By Impeding Cell Cycmentioning
confidence: 99%
“…Previous studies have revealed the role of cell cycle regulators in muscle biology ( Marroncelli et al, 2018 ; White et al, 2018 ). For example, p16 Ink4a , a CDK inhibitor, accelerated the entry of satellite cells into a senescent state ( Zhu et al, 2019 ), CDKN1c (p57 Kip2 ), a CDK inhibitor, coordinates the balance between proliferation and growth arrest in satellite cells ( Mademtzoglou et al, 2018 ), and the overexpression of CDK4 in human myoblasts was useful for immortalization and associated with the maintenance of cell proliferative capacity ( Zhu et al, 2007 ; Shiomi et al, 2011 ). However, the physiological roles of CDK1 in myogenesis and muscle regeneration have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%